Biliary fasciolosis: a report of three cases diagnosed by ERCP - Bahçecio?lu, Ibrahim Halil; Yalniz, Mehmet; Ataseven, Hüseyin; Kuzu, Nalan; Ilhan, Fulya; Erensoy, Ahmet (My University, 2008)
Fasciola hepatica is an endemic parasite in Turkey. Chronic Fasciola hepatica infestation is known to cause biliary obstruction and inflammation. Also, biliary fasciolosis may be asymptomatic. We report three patients with biliary fasciolosis who were diagnosed and managed by endoscopic retrograde cholangiopancreatography (ERCP). None of cases had eosinophilia. All cases were admitted to hospital with nonspecific symptoms. ERCP may be used for direct diagnosis and management of biliary fasciolosis.
Biliyer Fasciolosis: ERCP ile Tani Konulan Uç Olgu Raporu.
Keywords: Adult; Animals; Cholangiopancreatography, Endoscopic Retrograde; Endemic Diseases; Fascioliasis; Female; Humans; Middle Aged; Turkey; Young Adult; adult; animal; article; case report; endemic disease; endoscopic retrograde cholangiopancreatography; fascioliasis; female; human; middle aged; Turkey (republic)